Olaparib protects cardiomyocytes against oxidative stress and improves graft contractility during the early phase after heart transplantation in rats - Korkmaz-İçöz, Sevil; Li, Shiliang; Ruppert, Mihály; Lasitschka, Felix; Loganathan, Sivakkanan; Szabó, Gábor (British journal of pharmacology, 2018)
Background and Purpose Olaparib, rucaparib and niraparib, potent inhibitors of poly(ADP-ribose) polymerase (PARP) are approved as anti-cancer drugs in humans. Considering the previously demonstrated role of PARP in various forms of acute and chronic myocardial injury, we tested the effects of olaparib in in-vitro models of oxidative stress in cardiomyocytes, and in an in vivo model of cardiac transplantation. Experimental Approach H9c2-embryonic rat heart-derived myoblasts pretreated with vehicle or olaparib (10μM) were challenged with either hydrogen peroxide (H2O2) or with glucose oxidase (GOx, which generates H2O2 in the tissue culture medium). Cell viability assays (MTT, lactate dehydrogenase) and Western blotting for PARP and its product, PAR was performed. Heterotopic heart transplantation was performed in Lewis rats; recipients were treated either with vehicle or olaparib (10 mg kg-1). Left ventricular function of transplanted hearts was monitored via a Millar catheter. Multiple gene expression in the graft was measured by qPCR. Key Results Olaparib blocked autoPARylation of PARP1 and attenuated the rapid onset of death in H9c2 cells, induced by H2O2, but did not affect cell death following chronic, prolonged oxidative stress induced by GOx. In rats, after transplantation, left ventricular systolic and diastolic function were improved by olaparib. In the transplanted hearts, olaparib also reduced gene expression for c-jun, caspase-12, catalase, and NADPH oxidase-2. Conclusions and Implications Olaparib protected cardiomyocytes against oxidative stress and improved graft contractility in a rat model of heart transplantation. These findings raise the possibility of repurposing this clinically approved oncology drug, to be used in heart transplantation. Linked Articles This article is part of a themed section on Inventing New Therapies Without Reinventing the Wheel: The Power of Drug Repurposing. To view the other articles in this section visit http://onlinelibrary.wiley.com/doi/10.1111/bph.v175.2/issuetoc
First published: 14 August 2017
Gesehen am 24.10.2018